The Effect of Predictable and Unpredictable Training on the Speed of Footwork in Badminton - Febby Ardhia; Rizal Ahmad Fauzi; Dinar Dinangsit (UNIB Press, 2022)
Footwork is a movement that regulates the body to position the body in such a way that it makes it easier to perform the movement of hitting the shuttlecock according to its position. The purpose of this technique is so that the shuttlecock can be reached in any area quickly when the opponent attacks. The purpose of this study is to test how much influence predictable and unpredictable training is against the speed of footsteps in badminton games, this study used an experimental method with the pretest-posttest control and experimental group design. The population used was 30 students of UPI Sumedang badminton UKM, the samples taken were 10 students for experimental treatment and 10 students for control treatment using techniques. Based on the results of the data analysis obtained, the average pre-test experiment 65,80 and post-test 85 show an increase in the speed of footwork after being given an exercise using android court footwork. In addition, the increase in speed in badminton UKM Students can be seen from the N-Gain scores in both groups. The N-Gain score in the experimental groups was higher than the control group ( 56,85 > 31,78) and in the t-test, on the N-Gain value, the score obtained the Sig value. (2-tailed) = 0,001 < α = 0,05. So, it can be concluded that predictable and unpredictable training affects the speed of footwork of badminton UKM students and there is a significant difference in effectiveness in the application of android court footwork exercises with conventional exercise.